PENGARUH KUALITAS PRODUK, PROMOSI DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN BATIK PADA RUMAH BATIK DANAR HADI MELAWAI: indonesia - Saputra, Wisnu; Setiawan, Yuli (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2023)
This research aimed to determine the effect of Product Quality, Promotion, and BrandImage on Purchasing Decisions of Batik at the Rumag Batik Danar Hadi Melawai. Thepopulation in this study were all consumers of Rumah Batik Danar Hadi Melawai. The samplein this study amounted to 100 respondents. The design of this study used a casual design andquantitative methods. The data analysis method in this study is multiple linear regressionanalysis, F test, t test and coefficient of determination using SPSS 24.0 software.Simultaneously (F test) shows that there is a significant effect between Product Quality (X1),Promotion (X2), Brand Image (X3) variables on Purchase Decision (Y). The results of thisstudy indicate that partially (t test) Product Quality (X1) has a significant effect on PurchaseDecisions (Y), while Promotion (X2) and Brand Image have no and no significant effect onPurchase Decisions (Y).